1955
DOI: 10.1085/jgp.39.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Inhibition in an Isolated Nerve Cell

Abstract: Following the preceding studies on the mechanisms of excitation in stretch receptor cells of crayfish, this investigation analyzes inhibitory activity in the synapses formed by two neurons. The cell body of the receptor neuron is located in the periphery and sends dendrites into a fine muscle strand. The dendrites receive innervation through an accessory nerve fiber which has now been established to be inhibitory. There exists a direct peripheral inhibitory control mechanism which can modulate the activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
93
0

Year Published

1956
1956
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(99 citation statements)
references
References 19 publications
(33 reference statements)
6
93
0
Order By: Relevance
“…This suggests that the two antagonistic components of the response may not simply add algebraically. The hyperpolarization might be an IPSP that "shunts" the membrane thereby reducing the effectiveness of subsequent excitatory inputs (Kuffler and Eyzaguirre, 1955) or only part of the lateral effect from the surround might be fed forward to the ganglion cell in the form of a hyperpolarizing transient; another signal might be fed back to bipolars to limit the response. It was shown previously (Werblin, 1972) that an illuminated windmill pattern, when spinning in the far surround of the ganglion cell receptive field, was effective in antagonizing the central response.…”
Section: Separation Of the Depolarizing And Hyperpolarizing Transientmentioning
confidence: 99%
“…This suggests that the two antagonistic components of the response may not simply add algebraically. The hyperpolarization might be an IPSP that "shunts" the membrane thereby reducing the effectiveness of subsequent excitatory inputs (Kuffler and Eyzaguirre, 1955) or only part of the lateral effect from the surround might be fed forward to the ganglion cell in the form of a hyperpolarizing transient; another signal might be fed back to bipolars to limit the response. It was shown previously (Werblin, 1972) that an illuminated windmill pattern, when spinning in the far surround of the ganglion cell receptive field, was effective in antagonizing the central response.…”
Section: Separation Of the Depolarizing And Hyperpolarizing Transientmentioning
confidence: 99%
“…We feel inclined to construe the prolonged inhibitory effects observed in the presence of piperazine as a form of postinhibitory polarization or depression, a term introduced by Kuffler & Eyzaguirre (1955) to describe the delayed hyperpolarization and suppression of spike activity which follow the stimulation of the inhibitory axon in isolated neurone preparations from the stretch receptor of the crayfish. Although DRUG INHIBITION OF ASCARIS MUSCLE Fig.…”
mentioning
confidence: 99%
“…In some of the experiments described by Kuffler & Eyzaguirre (1955) the intervals separating the first few spikes after the postinhibitory polarization are lengthened, that is the rate of rise of the prepotentials is slowed down. This is what is shown in the lower record of Fig.…”
mentioning
confidence: 99%
“…d 3 57 P PROCEEDINGS OF THE PHYSIOLOGICAL between the present findings and the condition of precocious puberty knowil to occur in young children in association with certain hypothalamic tumours (see Bauer, 1954 (Brock, Coombs & Eccles, 1952), crayfish sensory neurones (Kuffler & Eyzaguirre, 1955) and Betz cells (Phillips, 1956). We have found that the discharge of cerebellar Purkinje cells in decerebrate cats may also be inhibited in this way.…”
Section: Proceedings Of the Physiologicalmentioning
confidence: 50%